ANALISIS KENDALA YANG TERJADI DALAM PELAKSANAAN KEGIATAN PELATIHAN GURU PEMBINA KOMPETENSI SAINS NASIONAL (KSN) DI KABUPATEN ACEH SINGKIL - Rizka Hasmi Nasution (JS (JURNAL SEKOLAH), 2021)
Abstract: The National Science Competition (KSN), previously known as the National Science Olympiad (OSN), is a National Science Competition (KSN) which is an annual competition held in Indonesia in the field of science for elementary, middle, and high school students and the equivalent. There are only two fields that are included in the science olympiad at the district/city level, national to the international level, namely Mathematics and Science.This study aims to determine the teacher's obstacles in guiding students in facing national science competencies in Aceh Singkil Regency. Analysis of activities using interviews and qualitative data methods obtained direct observation through filling out questionnaires to 48 supervising teachers. According to the results of observations, the main problems faced are the professional abilities of teachers who are still very low and the lack of support from school principals in supporting the implementation of KSN in schools.Keywords: Obstacles to KSN Activities, Teacher TrainingAbstrak: Kompetisi Sains Nasional (KSN), sebelumnya dikenal dengan sebutan Olimpiade Sains Nasional (OSN), adalah ajang Kompetisi Sains Nasional (KSN) adalah kompetisi tahunan yang diadakan di Indonesia dalam bidang sains untuk siswa SD, SMP, dan SMA serta yang sederajat. Hanya ada dua bidang yang diikutsertakan dalam olimpiade sains ditingkat kabupaten/Kota, nasional hingga ke tingkat Internasional yaitu Matematika dan IPA. Penelitian ini bertujuan untuk mengetahui kendala guru dalam membimbing siswa dalam menghadapi kompetensi sains nasional di Kabupaten Aceh singkil. Analisis kegiatan menggunakan wawancara dan metode data kualitatif diperoleh observasi langsung melalui pengisian Angket kepada 48 guru pembimbing. Menurut hasil observasi masalah utama yang dihadapi adalah kemampuan profesional guru yang masih sangat rendah dan kurangnya dukungan dari kepala sekolah dalam mengdukung pelaksanaan KSN disekolah.Kata kunci : Kendala Kegiatan KSN, Pelatihan Guru